DRIVING SUSTAINABLE TRADE: GREEN TECHNOLOGY IMPACT ON CHINA-ASEAN CROSS-BORDER TRADE - Lanlan Yang; Jain Yassin; Mohd Adzwin Faris Niasin; Yali Ding (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The growing cross-border economic ties between China and ASEAN countries has highlighted the importance of their respective trade landscapes. This study looks into this dynamic by studying panel data for both regions from 2000 to 2021. The study uses a fixed effects and gravity model to investigate the impact of green technology determinants on cross-border trade between China and ASEAN. The study’s findings provide important insights. Adoption of Green technology appears as a stimulus for ASEAN imports and export from China, with statistical significance. Nevertheless, the new innovation of green tehnology found to be delivering contradictory outcomes. In light of these findings, the paper offers policy recommendations based on the research findings. Recognizing the impact of green technology on Chinese imports, governments may consider measures to strengthen the integration of green technologies into ASEAN’s sectors. Similarly, insights into the export dimension could guide policies targeted at increasing ASEAN’s position in the Chinese market through green technology routes.